A Novel Technique Using Magnetic Resonance Imaging in the Supine and Prone Positions for Diagnosing Lumbar Adhesive Arachnoiditis: A Preliminary Study. Issue 1 (24th October 2019) - Tsuchida, Rikuhei; Sumitani, Masahiko; Azuma, Kenji; Abe, Hiroaki; Hozumi, Jun; Inoue, Reo; Oshima, Yasushi; Katano, Shuichi; Yamada, Yoshitsugu
Abstract: Background: Lumbar adhesive arachnoiditis is a debilitating neuropathic condition and is difficult to diagnose owing to lack of definitive diagnostic criteria. By focusing on the intrathecal mobility of nerve roots, we assessed whether useful diagnostic criteria could be established using MRI. Methods: Seventeen patients with a high risk for lumbar adhesive arachnoiditis and 18 no‐risk patients with chronic low back pain and/or leg pain participated in this study. The patients underwent MRI in both the supine and prone positions. Eleven axial T2‐weighted images between the L2 and L5/S levels were obtained, and the proportion of the low‐intensity area in the dorsal half to the total low‐intensity area in the dural sac was calculated for each axial view. Results: At some lumbar levels, the low‐intensity area in the dorsal half of the dural sac was relatively larger in patients with a high risk for lumbar adhesive arachnoiditis than in the no‐risk patients. In the no‐risk group, the proportion of the low‐intensity area in the dorsal half in the supine position was significantly higher than that in the prone position at all lumbar levels. However, in the high‐risk group, at some levels, the proportions were not significantly different in the dorsal half of the dural sac between the supine and prone positions. Conclusion: In patients with a known risk for lumbar adhesive arachnoiditis, nerve roots lose their potential to migrate in the dural sac in the gravitational force direction on MRI.